2022
DOI: 10.1055/a-1839-0355
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Coagulation Profile in Major Liver Resection for Cancer: A Prospective Observational Study

Abstract: Hepatectomy induced coagulation disturbances have been well studied over the past decade. Cumulative evidence supports the superiority of global coagulation analysis compared to conventional coagulation tests (i.e. PT or aPTT) for clinical decision making. Cancer, however, represents an acquired prothrombotic state and liver resection for cancer deserves a more thorough investigation. This prospective observational study was conducted to assess the perioperative coagulation status of patients undergoing majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition, the nutritional status of HCC patients was less affected than other digestive cancers, making ALB more reflective of long-term liver damage. Since most components of the coagulation system were synthesized in the liver, the coagulation state of patients was also closely related to liver function [ 38 ]. Many studies have found that coagulation status could reflect the clinical outcomes of various cancers, and PT and TT were both prognostic indicators for HCC patients in this study [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nutritional status of HCC patients was less affected than other digestive cancers, making ALB more reflective of long-term liver damage. Since most components of the coagulation system were synthesized in the liver, the coagulation state of patients was also closely related to liver function [ 38 ]. Many studies have found that coagulation status could reflect the clinical outcomes of various cancers, and PT and TT were both prognostic indicators for HCC patients in this study [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[39,40] However, this approach may not be suitable for all clinical scenarios, such as hemodynamically compromised procedures or operations with a risk of long-term complications. [41][42][43] Recently, minimally invasive surgery has been widely welcomed by patients because of its small trauma, light pain, and rapid recovery. [44,45] However, perioperative bleeding remains a thorny problem for minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39,40 ] However, this approach may not be suitable for all clinical scenarios, such as hemodynamically compromised procedures or operations with a risk of long‐term complications. [ 41–43 ]…”
Section: Introductionmentioning
confidence: 99%